1988
DOI: 10.1172/jci113469
|View full text |Cite
|
Sign up to set email alerts
|

Influence on immunoreactive folate-binding proteins of extracellular folate concentration in cultured human cells.

Abstract: The influence of extracellular folate concentration on cellular levels of the folate transport protein and its soluble product was studied directly in cultured human nasopharyngeal carcinoma (KB) cells. As determined by radioimmunoassay, levels of the folate transport protein and the soluble folate-binding protein were 58±17 (mean±SD) and 5±2 pmol/mg cell protein, respectively, in KB cells maintained in standard medium (containing 2,300 nM folic acid). These levels significantly increased to 182±34 and 26±6 pm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 43 publications
2
69
1
Order By: Relevance
“…Because these culture conditions ensured adequate delivery of folate to all cell lines used, the differential cisplatin responsiveness cannot be attributed to different availability of endogenous folates but instead might reflect differences in the capacity to use them. FBP expression levels have been reported to be inversely regulated by the extra-and intracellular folate concentration (Kamen et al, 1986;Kane et al, 1988) but, in our hands, only one (L-SKOV3) out of five ovarian carcinoma cell lines tested showed FBP up-modulation when adapted at physiological folate concentrations (20 nM) . In the same study, all the cell lines showed a marked decrease in endogenous folates compared with cells grown in standard medium (2.3 ,UM), and the amount of total folate in the cells was in general directly proportional to the level of membrane FBP expression, consistent with the concept that intracellular folate content is maintained primarily by FBP in low-folate cultured cells (Matsue et al, 1992 (Table).…”
Section: Discussioncontrasting
confidence: 51%
“…Because these culture conditions ensured adequate delivery of folate to all cell lines used, the differential cisplatin responsiveness cannot be attributed to different availability of endogenous folates but instead might reflect differences in the capacity to use them. FBP expression levels have been reported to be inversely regulated by the extra-and intracellular folate concentration (Kamen et al, 1986;Kane et al, 1988) but, in our hands, only one (L-SKOV3) out of five ovarian carcinoma cell lines tested showed FBP up-modulation when adapted at physiological folate concentrations (20 nM) . In the same study, all the cell lines showed a marked decrease in endogenous folates compared with cells grown in standard medium (2.3 ,UM), and the amount of total folate in the cells was in general directly proportional to the level of membrane FBP expression, consistent with the concept that intracellular folate content is maintained primarily by FBP in low-folate cultured cells (Matsue et al, 1992 (Table).…”
Section: Discussioncontrasting
confidence: 51%
“…The impact of FR expression on the activity of antifolates is influenced by the folate present and its concentration in vitro or in vivo and the relative affinities of the folate and antifolate for this transporter. Hence, in standard media with folic acid levels of 2.3 mm, transport of MTX via FRs is markedly suppressed, with a comparable decrease in growth inhibition by this agent due to the 300-fold higher affinity of folic acid for the receptor (Kane et al, 1986;Chung et al, 1993). Likewise, activity of the nonpolyglutamatable TS inhibitor, CB300638 which has a very high affinity for folate receptor but a low affinity for RFC, was marked suppressed when 1 mm folic acid was added to medium containing either 1 or 20 nm 5-CHO-THF (Theti et al, 2003).…”
Section: Folic Acid Receptor-mediated Transportmentioning
confidence: 99%
“…Many aspects of the cellular pharmacology of DDATHF have already been investigated in detail. DDATHF appears to be a good substrate for membrane folate-binding proteins (mFBP) (Kane et al, 1988;Westerhof et al, 1991), which probably act as a relevant carrier for its intracellular transport. The intracellular transport can also be mediated by the reduced folate carrier (Pizzorno et al, 1993).…”
mentioning
confidence: 99%